2015
DOI: 10.1371/journal.pone.0128907
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Unfavorable Treatment Outcomes in New and Previously Treated TB Patients in Uzbekistan: A Five Year Countrywide Study

Abstract: BackgroundTB is one of the main health priorities in Uzbekistan and relatively high rates of unfavorable treatment outcomes have recently been reported. This requires closer analysis to explain the reasons and recommend interventions to improve the situation. Thus, by using countrywide data this study sought to determine trends in unfavorable outcomes (lost-to-follow-ups, deaths and treatment failures) and describe their associations with socio-demographic and clinical factors.MethodA countrywide retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
49
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 17 publications
14
49
6
Order By: Relevance
“…This study was consistent with the finding in Uzbekistan (60%) [16], Turkey (65%) [17], and at Mizan-Aman general hospital (57.2%) [15]. These studies reported an outweighed disease proportion of male patients over female patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study was consistent with the finding in Uzbekistan (60%) [16], Turkey (65%) [17], and at Mizan-Aman general hospital (57.2%) [15]. These studies reported an outweighed disease proportion of male patients over female patients.…”
Section: Discussionsupporting
confidence: 91%
“…And this finding was almost similar with the study finding conducted in Uzbekistan. In this study, pulmonary TB (PTB) was present in 77%, of which 43% were smear-positive and 53% were smear-negative [16], with the study finding conducted at Mizan- Aman general hospital (51.05%) [15], and This finding was also supported with the study finding conducted in Kwekwe district, Zimbabwe. In this study 42.4% of patients were with pulmonary tuberculosis and 8.2% of patients were with extra pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 78%
“…The 31 included papers 10–40 comprised 35 datasets (one paper contained five separate datasets 19 ), representing 82,436 children diagnosed with tuberculosis, of whom 9,273 died (Table 1). Six studies were from the pre-treatment era, seven from the middle era, and 18 from the recent era; studies were from multiple geographic regions (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…A 5-year study in Uzbekistan reported that the urban population was at risk for treatment failure and LTFU. 15 Potential reasons could include MDR-TB, which could be more frequent among urban than rural TB patients, and is associated with more medical resources in urban areas, which may lead to incomplete treatment. 3,16 We found that those with an unknown DOT provider were more likely to be lost to follow-up, die or have a failed treatment outcome.…”
Section: Discussionmentioning
confidence: 99%